Diagnostics of Bronchial Asthma in Infants: Possibilities, Topical Issues, Differential Diagnosis - S.N. Nedelskaya; D.A. Yartseva (Zaslavsky O.Yu., 2013)
The review of the modern diagnostic methods of bronchial asthma in infants is presented. We described a methodological approach to diagnosis confirming by analyzing modern international and domestic protocols. Range of diseases with which the differential diagnosis should be done is shown.